State Secretaries Reform in Ukraine : Attempt to Delineate Responsibilities between Ministers and Senior Civil Servants - Balabushko, Oleksii (World Bank, Washington, DC, 2016)
The relationship between politicians and senior officials has been on the reform agenda in many countries, often on the premise that balance between technical, nonpartisan appointments and ensuring the responsiveness of public servants to the policies of the current government could be improved (Matheson et al. 2007). This paper examines an attempt to de-politicize senior civil service in Ukraine through the introduction of state secretaries, to understand whether the diagnosis of imbalance in this political/administrative interface was correct, and why the reform failed. The paper draws on a survey of government officials and experts as well as legal acts, available documents, articles, and personal interviews. The paper concludes that politicized civil service was a problem of form rather than function—the immediate problem was the undefined political role of the executive. It led to compression of the roles of policy makers and senior civil servants, making the reform ultimately irrelevant.